Producción musical del tema “Neo Albacito - Rivas Miranda, Saskya Alexandra (2013)
“Neo Albacito”, is a piece composed, directed and performed in 2007 by the Japanese Master Musician Tadashi Maeda, whose purpose was to innovate the Ecuadorian music by using polyrhythms. Such fusion is presented in this theme with the rythms of albazo and bomba. This theme has great versatility due to the characteristics of its composition. Since its release in Japan, it has been presented nationally and internationally in different music formats. It is written in a 6/8 meter and in the key of E minor. “Neo Albacito” was recorded in an acoustic format with the participation of experienced and renowned musicians playing the following instruments: contrabass, marimba, Andean bass drum, congas, güiro, bell, quena, guitar and violin. The use of these instruments, the flavor brought in by the percussion instruments and the impeccable execution by the musicians; contribute to making this piece more dynamic, cheerful and easier to relate to for the public...